Marital Conflict Management of Married Men and Women - Delatorre,Marina Zanella (2018)
Abstract This study aimed to investigate constructive and destructive conflict resolution strategies used by married women and men, as well as the association of these strategies with sociodemographic and relationship variables. Participants were 750 heterosexual couples living in Rio Grande do Sul, Brazil, who answered the Conflict Resolution Behavior Questionnaire - CRBQ and 16 questions about sociodemographic data and relationship characteristics. Variance and correlation analyses were conducted in order to verify the differences and associations between the study variables. The “compromise” conflict resolution strategy was used more by men compared to women, and women used the “attack” strategy more often when compared to men. For both, religiosity was correlated with constructive strategies, whereas having children was associated with destructive strategies. Considering these findings, the aspects that can favor constructive management of conflicts by spouses are discussed.